Multimedia assisted learning of Japanese kanji characters - Librenjak, Sara (Array, 2012)
This research presents guidelines for usage of multimedia in learning Japanese writing system for international learners. The writing system in question, the Sino-Japanese script called kanji, consists of at least 2000 commonly used ideograms. Such system presents a great obstacle in acquiring Japanese language for a great number of international learners. The research consists of three parts. Firstly, we provide an overview of existing multimedia tools for learning and teaching the Sino-Japanese script. Secondly, we present the results of survey among 47 international students. They have been surveyed about their methods of learning kanji in classroom and self-study, as well as their perceived difficulties and problems. Lastly, we talk about the experiment about using multimedia in teaching and learning kanji. The group of 6 students spent one semester learning kanji using modern multimedia method, such as websites, videos and smartphones. The group was successful in acquiring a large number (300-400) of characters with greater retention and reported enjoyment in the process, which had been the biggest issues in the acquisition process.